1996
DOI: 10.1097/00006534-199605000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Bleed of and Biologic Response to Triglyceride Filler Used in Radiolucent Breast Implants

Abstract: Radiolucent breast implants filled with triglyceride oil have recently entered limited clinical trials. To investigate the questions of oil bleed and the fate of triglycerides that might escape from ruptured breast implants, experiments reported here used peanut oil labeled with radioisotopes so that it could be traced in the urine, feces, and organs of two groups of rabbits. In one experiment, 18 rabbits were implanted with peanut oil-filled implants labeled with tritium to determine whether triglycerides dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 10 publications
0
13
1
1
Order By: Relevance
“…22 Other studies found the bleeding rate to be as high as 5 percent of the implant content per year. 13,23 The consequent underfilled implant could explain why rippling is so common in these women. Another possible explanation of the rippling in our series may be related to the textured elastomer, which was extremely adherent to the capsule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Other studies found the bleeding rate to be as high as 5 percent of the implant content per year. 13,23 The consequent underfilled implant could explain why rippling is so common in these women. Another possible explanation of the rippling in our series may be related to the textured elastomer, which was extremely adherent to the capsule.…”
Section: Resultsmentioning
confidence: 99%
“…12 A study in an animal model showed that no harmful effects were associated with use of this new filler material. 13 Other studies analyzed the oil collected from an explanted implant and demonstrated the formation of lipid peroxides. 14 In vitro investigations have shown that lipid peroxidation can lead to DNA alterations.…”
mentioning
confidence: 99%
“…4,[22][23][24][25] The soybean oil used in Trilucent implants consisted of 86% unsaturated fatty acids and less than 1% free fatty acids. Polyunsaturated and free fatty acids are susceptible to auto-oxidation, eventually leading to the formation of hydroperoxides.…”
Section: Oxidative Instability Of the Filler Materialsmentioning
confidence: 99%
“…[35][36][37] Given the known data on silicone elastomer degeneration secondary to lipid infiltration and the reports of bleeding of triglyceride filler in radiolucent breast implants, it is only logical to assume that triglycerides, being lipophilic compounds, are absorbed by the silicone elastomer, resulting in a loss of shell integrity because of a decrease in tensile strength and also resulting in increased permeability. 22,33 Peters and Smith, 38 in an invited discussion, reviewed lipid absorption and infiltration in various surfaces and ended by stating, "If lipid absorption proves to be a significant problem, then new prostheses containing vegetable or other oils will require a more critical evaluation. "…”
Section: Unifying Hypothesismentioning
confidence: 99%
“…No clinical trials of them were held prior to market approval in Europe, and after their withdrawal from the market the post-market trial was halted. 60 Subsequently, the company with responsibility for the Trilucent implant (AEI Inc.) has enrolled women who have had them into a research program to look at the long-term effects. 61 Interestingly, in the US, a clinical trial using Trilucent implants was set up (but not yet published), although the device was never approved for commercial use there.…”
Section: Experimenting On Womenmentioning
confidence: 99%